THE RELATIONSHIP AMONG LEARNING FACILITIES, THE LOGICAL THINKING ABILITY AND PARENT’S GUIDANCE WITH LEARNING ACHIEVEMENT OF MATHEMATICS STUDENTS CLASS XI - Sinta Susanti; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
Low students are learning achievement of mathematics associated with many factors. The relationship among Learning Facilities, The Logical Thinking Ability, and Parent’s Guidance are some of the factors allegedly related to the learning achievement of mathematics. This research aims to determine the presence or absence of positive and significant relationships among Learning Facilities, The Logical Thinking Ability, and Parent’s Guidance with Learning Achievement of Mathematics Students Class XI IPS in Even Semester SMA Muhammadiyah 5 Yogyakarta Academic Year 2016/2017. The population in this research was the students of class XI IPS in even semester SMA Muhammadiyah 5 Yogyakarta academic year 2016/2017, consisted of class XI IPS 1, XI IPS 2, XI IPS 3, XI IPS 4 totaling 111 students. Samples were taken from class XI IPS 1 as the research sample class and the random sampling technique. Technique data collection using documentation method, questionnaire method, and test method. The research instrument use validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of independence, and a linearity test. The writer uses linear regression analysis and correlation analysis. The results showed that there was a positive and significant relationship among Learning Facilities, The Logical Thinking Ability, and Parent’s Guidance with Learning Achievement of Mathematics Students Class XI IPS in Even Semester SMA Muhammadiyah 5 Yogyakarta Academic Year 2016/2017. It is showed by is and 2,99 with Coefficient of multiple correlation ( ) amount 0,880 and coefficient determination double amount 0,775 with the linear regression equation . 29,315%, and and and .